CLEF 2.0. Solutions for Native Linked Data Cataloguing of Italian Digital Cultural Heritage - Sebastiano Giacomini; Marilena Daquino; Francesca Tomasi; Laurent Antoine Fintoni (JLIS.it)
The Semantic Web had a significant impact on the GLAM domain, where the need to connect knowledge has grown so important that it has sparked numerous crowdsourcing initiatives and collaborative native Linked Open Data cataloguing projects. One of the key challenges in facing these collaborative activities is the heterogeneity of content and levels of expertise among users. While existing solutions can meet several important requirements, developing new features is often affected by the practical use of such platforms in real-world work settings. This article explores novel demands and presents the solution proposed by CLEF 2.0, the native Linked Open Data cataloguing software adopted in various case studies concerning the description of Italian Digital Cultural Heritage.